How to grow Renova's business out of the tissue in Portugal?: marketing plan - Figueiredo, Beatriz (2020)
Market leader in the tissue category in Portugal, Renova is a well renowned brand in its home market. Focused on maintaining its leading position, the company has expressed interest in exploring new opportunities outside its core business, while staying within its current distribution network. Careful industry analysis of the two main categories home care and beauty and personal care identified a potential growth opportunity within the men’s grooming category. The proposed concept for ‘Renova Men’ revolves around the concept of well-being and feeling good in an approach to liberalize men from outdated stereotypes. A marketing plan for the implementation of the concept is suggested, including an Integrated Marketing Communications Plan.